CRITICAL THINKING AND POSSIBILITIES OF ITS DEVELOMENT IN TECHNICAL SUBJECTS AT ELEMENTARY SCHOOLS - PLISCHKE, Jitka; KROPAC, Jiri (Trends in education, 2010)
Critical thinking is a prerequisite for successful technical thinking and the ability to evaluate technology in an appropriate way. The article pays attention to the term ´critical thinking´ and its development conditions in technical subjects teaching at elementary schools. The authors also elaborate the main approaches to incorporate critical thinking and they present possibilities to apply critical thinking when using thinking strategies and learning EUR in a lesson about water taps.
Keywords: technical subjects; critical thinking; thinking strategies and learning EUR.